PENGEMBANGAN BAHAN AJAR E-MODUL MATA PELAJARAN MESIN PENGGERAK UTAMA KAPAL - Mahzuardi; Refdinal; Ambiyar; Hasan Maksum (Jurnal Penelitian Pendidikan IPA, 2024)
The designed e-module is expected to meet these needs by presenting interactive, easily accessible, and interesting learning materials. This study aims to utilize advances in digital technology in improving the quality of vocational education and preparing students according to the needs of modern industry. The method used in this study is the Research and Development (R&D) approach by following the ADDIE model, which includes the stages of Analyze, Design, Develop, Implement, and Evaluate. The stages begin with a needs analysis to identify the specifications of the required teaching materials and the characteristics of the students. At the Design stage, the e-module is designed with an attractive structure and relevant materials. Then the initial product development is carried out, followed by evaluation by material, language, and IT experts to ensure the quality of the e-module. Implementation involves limited trials in the school environment to collect feedback and assess the effectiveness of the e-module in the learning process. The data analysis technique in this study uses a validation sheet. The results of the study indicate that the developed e-module has a high level of validity, practicality, and effectiveness in the learning process. Expert validation gave a score of 100% for material, 98% for language, and 93% for media/IT, indicating excellent quality. Field trials by teachers resulted in a score of 92%, while broader trials with learners resulted in a score of 97%, both indicating a high level of effectiveness and acceptance of the e-module. In conclusion, the development of IT-based e-modules has proven effective in improving the quality and motivation of learning, in accordance with the demands of vocational education that is adaptive and responsive to technological developments.